1996
DOI: 10.1115/1.2796045
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Loading Conditions and Fracture Patterns of the Proximal Femur

Abstract: In an attempt to test the hypothesis of spontaneous hip fracture, seven pairs of femurs, with ages ranging from 59 to 90, were tested under two loading conditions designed to simulate muscular contraction. Simulated iliopsoas contraction produced femoral neck fractures at an average normalized ultimate load of 5.2 +/- 0.8 times body weight. Simulated gluteus medius contraction produced sub-/inter-trochanteric fractures at an average normalized ultimate load of 4.1 +/- 0.6 times body weight. The average ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Several studies showed that bone exhibits a quasi-brittle material behavior [5,14,16,[32][33][34]62] or brittle behavior [31,43,68,88] depending mainly on the deformation rate applied and the bone properties. Therefore, more suitable physical models are still lacking to describe the brittle to quasi-brittle fracture behavior of human femur.…”
Section: Previous Fe Models Have Applied Different Uncoupled Fracturementioning
confidence: 99%
“…Several studies showed that bone exhibits a quasi-brittle material behavior [5,14,16,[32][33][34]62] or brittle behavior [31,43,68,88] depending mainly on the deformation rate applied and the bone properties. Therefore, more suitable physical models are still lacking to describe the brittle to quasi-brittle fracture behavior of human femur.…”
Section: Previous Fe Models Have Applied Different Uncoupled Fracturementioning
confidence: 99%
“…But it has been suggested that when neuromotor control is sub-optimal, the forces transferred to the skeleton during normal daily activities can considerably increase , thus inducing overloading. Moreover, (Yang et al, 1996) developed an in vitro simulation to determine a possible biomechanical background for spontaneous hip fractures, concluding that abnormal muscle contraction of the rotator muscles could induce hip fracture. If these conjectures are true, then truly spontaneous fracture could be possible, at least in principle.…”
Section: Introductionmentioning
confidence: 99%
“…Regression analysis was also used to examine the correlation between fracture forces and geometric parameters. Finally, using post-fracture CT scans, we classified the femoral fractures into subcapital, transcervical, intertrochanteric and pertrochanteric based on Müller AO Classification of Fractures-Long Bones [15]. We used ANOVA to compare the fracture types of femora with different aBMD.…”
Section: Methodsmentioning
confidence: 99%